AN ANALYSIS OF THE DEMAND OF WEATHER INDEX-BASED INSURANCE WITH FLEXIBLE ATTRIBUTES IN A RISK MANAGEMENT FRAMEWORK - Castellani, Davide; Vigano, Laura (European Scientific Journal, ESJ, 2015)
We propose a rural household’s risk management framework to investigate whether the low take-up of index-based insurance may depend, first, on the heterogeneity of the product’s attributes and, second, on a substitution effect between the insurance and on-farm and off-farm risk management strategies. We conducted a discrete choice experiment in Ethiopia with a sample of farmers using a weather security with fixed compensation in case of drought. We offered securities with different combinations of attributes: premium, compensation, preferred season, frequency of drought, sale location, and time of premium payment, allowing for interest payment and administration and distribution costs. We used a Mixed Logit Model. We find that while available risk management strategies are not important in the decision to buy insurance, heterogeneity in the demand is remarkable and relies on the indemnity and home delivery attributes, the type of drought insurance (for moderate or severe drought), and the capacity to appreciate the value of insurance.